Low Frequency Noise Measurement and Analysis of Capacitive Micro-Accelerometers: Temperature Effect - Mohd Yasin, Faisal; Nagel, David J.; Ong, D. S.; Korman, Can E.; Chuah, Hean Teik (IOP Publishing, 2008)
A noise measurements of micro-accelerometers were performed using a special measurement system. A common spectral behavior of noise is found, with 1/f noise dominating at low frequencies and white thermal noise being the limiting factor at higher frequencies. A temperature dependent and an acceleration dependant of the noise are found in the accelerometers, in agreement and contract of the theories, respectively.